Determinação de macro, microelementos e avaliação de risco à saúde humana a partir do consumo de plantas medicinais: Bauhinia forficata, Eleusine indica, Synadenium grantii e Orthosiphon stamineus - Souza, Igor Domingos de (2021)
The main objective of this work was to analyze the mineral composition and toxicity of micro and macro elements in the structural conformation of latex, leaves, medicinal plants Synadenium grantiiHook, Orthosiphon stamineus Benth, Bauhinia forficata subsp. pruinosa (vogel) and Eleusine Indica, used, in turn, as a therapeutic resource by rural and urban communities in the municipality of Campo Grande, Mato Grosso do Sul, Brazil. The methodology used in the execution of the research consisted of using analytical grade reagents, all equipment previously calibrated / enabled for use; collection and analysis of plant species (latex of Synadenium grantii) in the urban area of the city of Campo Grande / MS (coordinates 20 ° 28'43 "S and 54 ° 38'28" W, altitude 551 m); in the case of vegetable species Orthosiphon stamineus Benth, Bauhinia forficata subsp. pruinosa (vogel), these were acquired from the company of Natural Products and Medicinal Herbs - Chá e Cia- SP. The plant species Eleusine indica was purchased from the Natural Products company - Sitio Menino Vaqueiro, Itapipoca, Ceará. The results obtained call attention to the need for more research carried out with the so-called medicinal plants, of such common use among different Brazilian communities, located both in the countryside, in the rural area, as well as in the city, in the urban area. it is known that for the raw leaves, the elements potassium, magnesium and sodium showed values of QR and HI in ranges considered to be at risk of intoxication. As for leaf tea, only the phosphorus macro element showed QR values at risk levels. In the case of Eleusine indica, it was found in the present study the macro and microelements sodium, aluminum, iron, zinc, manganese, cobalt, copper, nickel and selenium, as well as the determination of the risk index for consumption.